A meta‐surface loaded, low profile 28 GHz phased array antenna. Issue 1 (28th October 2021) - Hussain, Sajjad; Qu, Shi‐Wei; Bu, Dinuo; Wang, Xiao‐Hua; Sharif, Abu Bakar
Abstract: A low‐profile wide‐scan phased array for 28 GHz 5G band operation, based on the current sheet array (CSA) concept, is presented in this work. The array is dual‐polarized with horizontally and vertically polarized dipoles are placed in close proximity to leverage intentional capacitive coupling. A meta‐surface based on fully split rings is printed on the top of the matching layer, contributing to wide‐scan performance. A capacitive metallic plate is placed below the cross‐section formed between orthogonal dipole elements to subdue the in‐band coupled‐loop modes. The design is demonstrated to operate at 26–30 GHz with voltage standing wave ratio (VSWR) <3 for ±60° scanning in principal planes, with a low‐profile 0.26λh . The simulations are validated by measuring an 8 × 8 array prototype, which shows good agreement with the simulated predictions.